A Missed Opportunity?: NOAA's Use of Social Media to Communicate Climate Science. Issue 2 (17th February 2018) - Lee, Nicole M.; VanDyke, Matthew S.; Cummins, R. Glenn
ABSTRACT: In the current media landscape, organizations often communicate about science directly with publics through online channels rather than relying on journalist gatekeepers. Online platforms present organizations with the opportunity to participate in two-way communication in order to increase engagement with science. The present study examined how the National Oceanic and Atmospheric Administration (NOAA) utilizes social media to interact with publics. Results suggest that NOAA does not fully utilize the dialogic potential of social media, which could enhance both the public's science literacy and trust in science regarding climate change specifically. This study informs how public relations theory may complement science communication theory and practice as deficit model-thinking transitions to contemporary approaches for public engagement with science.